Values clarification - "Simon, Sidney B." (New York, 1978)
Are you getting what you want out of life? Do you know where you draw the line when it comes to sex, money, cheating on your income tax ... or accepting an indecent proposal? Becoming aware of your values is the key to making wise choices in all aspects of your life, from picking a partner to buying a house. Created by Dr. Sidney Simon, coauthor of the bestselling Getting Unstuck, and two other leading professionals, this workbook has already had an impact on hundreds of thousands of lives. Its scores of intriguing, interactive exercises were designed to uncover the hidden beliefs that reveal what matters most to you, how you deal with life-changing conflicts, which career choices will make you happiest, what leisure time activities provide you with the most pleasure, where you honestly stand on controversial issues, what day-to-day events are likely to make you angry ... excited ... anxious ... confident, how best to motivate yourself, and what beliefs can cause conflict in your family or love relationship.
Keywords: Philosophy